UTILIZATION OF MICRO SISAL FIBERS AS REINFORCEMENT AGENT AND POLYPROPYLENE OR POLYLACTIC ACID AS POLYMER MATRICES IN BIOCOMPOSITES MANUFACTURE - Subyakto Subyakto; Nanang Masruchin; Kurnia Wiji Prasetiyo; Ismadi Ismadi (Indonesian Journal of Forestry Research, 2013)
Sisal (Agave sisalana) as a perennial tropical plant grows abundantly in Indonesia. Its fibers can be used as the reinforcement agent of biocomposite products. Utilization of sisal as natural fiber has some notable benefits compared to synthetic fibers, such as renewable, light in weight, and low in cost. Manufacture of biocomposite requires the use of matrix such as thermoplastic polymer, e.g. polypropylene (PP) and polylactic acid (PLA) to bond together with the reinforcement agent (e.g. sisal fibers). In relevant, experiment was conducted on biocomposites manufacture that comprised sisal fibers and PP as well as PLA. Sisal fibers were converted into pulp, then refined to micro-size fibrillated fibers such that their diameter reduced to about 10 μm, and dried in an oven. The dry microfibrillated sisal pulp fibers cellulose (MSFC) were thoroughly mixed with either PP or PLA with varying ratios of MSFC/PP as well as MSFC/PLA, and then shaped into the mat (i.e. MSFC-PP and MSFC-PLA biocomposites). Two kinds of shaping was employed, i.e. hot-press molding and injection molding. In the hot-press molding, the ratio of  MSFC/PP as well as MSFC/PLA ranged about 30/70-50/50. Meanwhile in the injection (employed only on assembling the MSFC-PLA biocomposite), the ratio of MSFC/PLA varied about 10/90-30/70. The resulting shaped MSFC-PP and MSFC-PLA biocomposites were then tested of its physical and mechanical properties. With the hot-press molding device, the physical and mechanical (strength) properties of MSFC-PLA biocomposite were higher than those of  MSFC-PP biocomposite. The optimum ratio of  MSFC/PP as well as MSFC/PLA reached concurrently at 40/60. The strengths of MSFC-PP as well as MSFC-PLA biocomposites were greater than those of individual polymer (PP and PLA). With the injection molding device, only the MSFC-PLA  biocomposite  was formed  and its strengths  reached  maximum  at 30/70  ratio.  The particular strengths (MOR and MOE) of MSFC-PLA biocomposite shaped with injection molding were lower than those with hot-press molding, both at 30/70 ratio. The overall MOR of such MSFC- PLA biocomposite was lower than that of pure PLA, while its MOE was still mostly higher.